AB1224-HPR Type of Personality – a New Item to Take into Account When Evaluating Quality of Life and Disease Activity in Rheumatoid Arthritis (RA) Patients. (9th June 2015) - Dobrin, M.A.; Donisan, T.; Predeteanu, D.; Bojinca, V.C.; Constantinescu, C.; Bojinca, M.; Opris, D.; Groseanu, L.; Borangiu, A.; Negru, M.; Berghea, F.; Balanescu, D.V.; et al.
Abstract : Background: In RA pts, health-related quality of life (HRQoL) assessment is important, but there is little research regarding the relation between the type of personality and the individual differences in HRQoL 1 . Optimism and the tendency to hold greater positive outcome expectancies have been found to be related with better psychological well-being in RA pts, while negative affectivity (components of type C and D personality) are reported to show lower health satisfaction scores 2 . Objectives: The aim of the present study was to investigate the association of different types of personality with aspects of HRQoL and disease activity in RA pts. Methods: This cross-sectional study included 104 RA pts from two different Rheumatology Departments (7.7% men, 92.3% women, mean age 59.08, mean duration of disease 12.77 years). Personality type was assessed with Jenkins Activity Survey for type A/B, State-Trait Anger Expression Inventory Anger-in Scale (AIS) for type C and Type D Personality Scale (DS14), with its components (negative affect-NA and social inhibition-SI) for type D. HRQoL was quantified using the Medical Outcome Study Short-Term-36 (SF36v2) and its subscales (Physical function-PF, Social function-SF, Role physical-RP, Role emotional-RE, Mental health-MH, Vitality-VT, Bodily Pain-BP, Global Health-GH, physical component scores-PCS and mental component scores-MCS). Disease activity was evaluated with Disease Activity Score (DAS28) and visual analog scale (VAS) for pain. Results: Type C pts correlate with decreases in HRQoL in 7 of its 8 subscales when compared to non-C personality pts (RP M =15±28.56/ M =3.14±38, VT M =32.57±2.23/ M =44.63±22.68, RE M =27.62±39.18/ M =49.99±44.05, MH M =39.54±25.88/ M =62.64±22.44, MCS M =36.98±13.33/ M =46.52±12.36; p<0, 05), whereas type D pts show lower values only in 5 of 8 components when compared to non-D (RP M =4.68±1/ M =29.06±37.54, GH M =28.75±13.6/ M =38.63±23.99, VT M =25±17.88/ M =43.83±21.93, SF M =49.21±27.18/ M =63.6±25.18, RE M =8.33±19.24/ M =49.22±43.9, MH M =26.75±22.75/ M =6.51±22.71, MCS M =29.89±11.17/ M =45.98±12.22; p<0, 05). Less features of type C associate with better MH (r=-.58) and less type D traits (smaller the NA and SI) with better MCS (rNA =-.55, rSI =-.38). Type C and D pts also have increased disease activity levels, not only related to DAS28, but also to PGA. Type A pts assess pain by VAS to be lower than those with type B (M=56.5±34.94 vs 84.66±15.09, p<0, 05), with no other significant correlations. Conclusions: The present study showed associations between type C and D personalities with negative effects on several components of HRQoL in RA pts and also with higher disease activity. We did not find significant correlations with type A personality, except for a lower pain assessment. Future research including prospective follow-up assessments is needed in order to determine if the personality type influences the evolution of disease and the response to treatment in RA patients. References: Uhlig T., et al. Rheumatology. 2007;34(6):1241-1247. Treharne GJ, et al. Br J Health Psychol.2007;12(1):323–345. Disclosure of Interest: None declared